Assessment of the efficacy of Bacillus thuringiensis and Pseudomonas fluorescens in the biological control of Hypera postica larvae and adults - Al-Nuaimy, Wafaa Ayad; Wali, Hawraa F; Al-Oebady, Mouna Akeel Hamed (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The research aimed to assess the impact of two bacterial isolates, Bacillus thuringiensis and Pseudomonas fluorescens, on the larvae and adults of Hypera postica in a laboratory setting, utilising three concentrations (1×10², 1×10⁴, and 1×10⁶) CFU / ml for both bacterial kinds under investigation. The study’s results indicated that the quantities employed varied in their efficacy in exterminating larvae and adults of the clover weevil H. postica in a laboratory setting. The findings indicated that the rates of mortality escalate with higher concentrations and prolonged feeding durations. The concentration of 1×106 CFU / ml of the B. thuringiensis exhibited the highest mortality rates after 96 hours of treatment, with rates of (75.8%, 73.9%, 69.7%, 68.2%, and 43.5%) for the first, second, third, fourth larval stages, and adults, respectively. In contrast, the lowest mortality rate was observed with the bacterium P. fluorescens at a concentration of 1×102 CFU / ml after 48 hours, yielding rates of (13.5%, 28.4%, 27.7%, 27.0%, and 6.6%) Subsequent to the aforementioned stages.